1924 Anayasası döneminde siyasal muhalefet - (:unkn) unknown (My University, 2015)
Batı demokrasilerini totaliter sistemlerden ayıran önemli unsurlardan biri siyasal muhalefettir. Çoğunlukçu demokrasilerde, iktidardaki parti dışında siyasi partiler var olmasına rağmen, seçimlerde iktidar partisiyle diğer partiler eşit koşullar içinde yarışamazlar. 1924 Anayasası da çoğunlukçu rejim örneğidir. Meclis, 1924 Anayasası'nda egemenliğin kullanılmasında tek yetkili organ olarak düzenlemiştir. Cumhuriyetin ilanının ardından kabul edilen Anayasa'da meclisin iradesinin sınırlanması düşünülmemiştir. Bu nedenle de meclisin Anayasaya uygunluğunu denetleyecek yargısal bir organa yer verilmemiştir. Özgürlüklerin yegane güvencesi, egemenliğin kullanıcısı TBMM olmuştur. Ayrıca 1924 Anayasası'nın uygulandığı tek partili dönemde, egemenliği kullanan organların çokluğu ve çok partili yaşam söz konusu değildi.

The political opposition is the one of the most distinctive subject to separate western democracies from totalitarian regimes. Even though there are other political parties besides of government party, not all these parties compete under equal conditions in majoritarian democracies. The Constitution of 1924 is an example of the majoritarian democracy. The Assembly was organized as the sole competent authority in the exercise of the sovereignty by the Constitution of 1924. After the proclamation of the Republic, the limitation of the Assembly's will was not considered in the Constitution. Therefore, there was not any judicial organ which supervises the constitutionality of the Assembly in the Constitution. The only guarantee of the freedom had been the Assembly exercising the sovereignty. In addition to this, in the Constitution of 1924 which was the single political party era, the multiplicity of organs to exercise of sovereignty and multi political party period was out of the question.
(Political Opposition in the Era of the Constitution of 1924)
Keywords: Hukuk